2019
DOI: 10.29252/johe.8.2.94
|View full text |Cite
|
Sign up to set email alerts
|

Quality of work life and its association with job burnout and job performance among Iranian healthcare employees in Islamabad-e Gharb, 2016

Abstract: Article Info Background: Health care centers play an important role in providing health service to the public and maintaining the health of the community. This study was an attempt to evaluate the quality of work life and its association with job burnout and job performance among healthcare employees. Material and Methods: This cross-sectional study was carried out on 136 employees of healthcare centers and health homes in Islamabad-e Gharb in 2016. The data collection tools were a demographic characteristics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 19 publications
1
4
1
2
Order By: Relevance
“…However, when staff is trained in EI, they significantly improve the quality of care, psychological empowerment, and overall well-being (Karimi et al, 2015). https://doi.org/10.56294/sctconf2023565 Similar to our study, a significant positive association was found between quality of life and work performance in workers from health centers and hospitals (Rastegari et al, 2010;Bakhshi et al, 2019). This suggests that as work-life quality increases, so does performance (Suyantiningsih et al, 2018;Nursalam et al, 2018).…”
Section: Discussionsupporting
confidence: 77%
“…However, when staff is trained in EI, they significantly improve the quality of care, psychological empowerment, and overall well-being (Karimi et al, 2015). https://doi.org/10.56294/sctconf2023565 Similar to our study, a significant positive association was found between quality of life and work performance in workers from health centers and hospitals (Rastegari et al, 2010;Bakhshi et al, 2019). This suggests that as work-life quality increases, so does performance (Suyantiningsih et al, 2018;Nursalam et al, 2018).…”
Section: Discussionsupporting
confidence: 77%
“…Another studies highlighted that faculty members experienced a lower quality of work life compared to other university employees, often citing unfavorable working conditions, lack of control and participation in decision-making, and low organizational commitment as contributing factors [ 40 , 41 ]. Additionally, Bakhshi et al found a direct relationship between the academic staff members' educational level and their perception of quality of work life [ 33 ]. It is important to note that the inconsistencies observed across different studies could potentially be attributed to variations in populations studied [ 40 , 42 ] and the instruments utilized for assessment [ 43 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…De forma adicional, la baja calidad de vida en el trabajo se ha asociado a efectos negativos como el estrés, problemas de salud física, mental, conductual y a nivel social (Durán, 2010), los hallazgos han confirmado su relación con el estrés, el síndrome de burnout y la depresión en personal hospitalario (Azevedo et al, 2017;Bakhshi et al, 2018;Bragard et al, 2015;Sh & Sh, 2014); también, se ha encontrado que la ansiedad está asociada a la mala calidad de vida en el trabajo, dichos hallazgos se han hecho principalmente en personal sanitario (Dehkordi et al, 2020;Hegney et al, 2014) y en personal docente (Bell et al, 2012).…”
Section: Recomendacionesunclassified
“…• 113 • res negativos en el trabajo (Bakhshi et al, 2018;Dehkordi et al, 2020), sin embargo, es necesario reconocer que la calidad de vida en el trabajo no puede solo limitarse a estos espacios laborales, pues es un fenómeno que puede presentarse en otros ámbitos y la única condición imperante es que los trabajadores se encuentren inmersos en una organización laboral (Leitão et al, 2019). Además, se reconoce que existen factores atributivos del trabajador, así como características laborales que aún no han sido profundizadas en los hallazgos empíricos.…”
Section: Recomendacionesunclassified